To evaluate the efficacy of subconjunctival bevacizumab injection in vascular pterygium before surgical excision in preventing recurrence comparing with bare sclera technique - Nusrat Shaheen; Abdul Gafoor Ahmed; Sheikh Sajjad; Wasim Rashid; Aamir Rashid (Journal of Clinical Ophthalmology and Research)
Introduction: Despite the growing body of evidence supporting the efficacy of subconjunctival bevacizumab injection, questions remain regarding its comparative effectiveness against conventional surgical techniques. Aims and Objectives: The aim of the study was to evaluate the efficacy of subconjunctival bevacizumab injection before pterygium surgery with bare sclera technique in preventing postoperative reoccurrence. Materials and Methods: The present study was a comparative, randomized prospective study. Patients included were divided into two groups of 50 patients each. Patients in Group A received bevacizumab 2.5 mg/0.1 ml, and patients in Group B received subconjunctival balanced salt solution 0.1 ml. The primary outcome was recurrence of pterygium at 6 weeks and 6 months. Results: The total number of patients was 100. The mean age was 36.9 ± 8.67 years. The left eye was involved in more, i.e., 61 than the right eye 39. Majority of patients in Group A, i.e., 30 (60%) and in Group B 31 (62%) had Grade 2 pterygium, followed by Grade 3 pterygium in 17 (34%) in Group A and 15 (30%) in Group B. The recurrence rate at 6 weeks was 6% (3 patients) in Group A while it was 22% (11 patients) in Group B (P = 0.021). The recurrence rate at 6 months was 8% (4 patients) in Group A while it was 26% (13 patients) in Group B (P = 0.017). Conclusion: Subconjunctival injection of bevacizumab before surgery of pterygium is safe and effective in terms of recurrence and the complication rate for primary or recurrent pterygium treatment.